Sovietization of Armenia in 1920 and Sergo Ordzhonikidze - V. Mukhanov (Международная аналитика, 2017)
The article discusses the situation in the Caucasus that established by the summer of 1920, after the successful and rapid sovietization of Azerbaijan, as well as the actions of the Caucasus Bureau of the party, headed by Sergo Ordzhonikidze. Another focus of the article is the decision-making process in Moscow on the sovietization of Armenia and the relevant contacts with the new Turkish government of Mustafa Kemal. The article highlights the differences that existed within the Soviet leadership on the question of choosing the political line in relations with Armenia, and analyzes the position and actons of S. Ordzhonikidze, head of the Caucasian Bureau, who played a key role in the sovietization of the entire Transcaucasus region.